Influência da variação geométrica dos alvéolos na capacidade resistente ao cisalhamento de lajes alveolares protendidas - Maciel, Andrey Monteiro (2017)
This dissertation deals with the study of the influence of void geometry on the shear capacity of prestressed hollow core slabs. Based on analytical models for the tension shear capacity for uncracked sections, which were first proposed by YANG (1994) and latter modified by PAJARI (2005), a calculation procedure applying spreadsheets has being proposed for the prior definition of the void geometry, allowing an easy and quick way to evaluate the efficiency of the void shape to provide shear capacity. In addition, the influence of the variation of the angle of failure for the tension shear mechanism has been confronted against experimental results, giving indication that the fixed angle of 35º assumed by YANG (1994) is an adequate inclination to be considered in design. Calculation examples were presented in order to elucidate the main concepts discussed in this work. Comparisons were made considering the Brazilian normative model and the Yang-Pajari model for tension shear, from results obtained experimentally for prototypes whose rupture occurred by diagonal traction, and for the Brazilian standard model, safety results were not verified for slabs with oblong cores; as opposed to the YANG-PAJARI model applied to the same slabs, providing satisfactory results. In addition, the analytical model based on the Brazilian code of practice for structural concrete has been verified against experimental results for slabs with oblong cores, wherein some of the experimental results were found below the predicted values. However, as the number of experimental results was small, future experimental investigation is needed in order to verify the reliability of this analytical model.